2021
DOI: 10.1038/s41419-021-03426-z
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90-stabilized MIF supports tumor progression via macrophage recruitment and angiogenesis in colorectal cancer

Abstract: Macrophage migration inhibitory factor (MIF) is an upstream regulator of innate immunity, but its expression is increased in some cancers via stabilization with HSP90-associated chaperones. Here, we show that MIF stabilization is tumor-specific in an acute colitis-associated colorectal cancer (CRC) mouse model, leading to tumor-specific functions and selective therapeutic vulnerabilities. Therefore, we demonstrate that a Mif deletion reduced CRC tumor growth. Further, we define a dual role for MIF in CRC tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 74 publications
(61 reference statements)
3
29
0
Order By: Relevance
“…A key prerequisite for the gain-of-function (GOF) of some missense p53 mutants is protein stabilization through the Hsp90 chaperone machinery. Importantly, the clinically relevant Hsp90 inhibitors Ganetespib or Onalespib provide therapeutic selectivity toward tumor epithelial cells but not normal cells, making them attractive for anti-cancer therapies (44). Furthermore, in other cellular contexts such as lymphoma ( 23), treatment with the Hsp90 inhibitor Ganetespib downregulated mutp53 protein levels.…”
Section: Results P53 Missense Mutants In Human Pdac Cell Lines Are Stabilized Via Hsp90mentioning
confidence: 99%
“…A key prerequisite for the gain-of-function (GOF) of some missense p53 mutants is protein stabilization through the Hsp90 chaperone machinery. Importantly, the clinically relevant Hsp90 inhibitors Ganetespib or Onalespib provide therapeutic selectivity toward tumor epithelial cells but not normal cells, making them attractive for anti-cancer therapies (44). Furthermore, in other cellular contexts such as lymphoma ( 23), treatment with the Hsp90 inhibitor Ganetespib downregulated mutp53 protein levels.…”
Section: Results P53 Missense Mutants In Human Pdac Cell Lines Are Stabilized Via Hsp90mentioning
confidence: 99%
“…We found that MIF-(CD44-CD74) pairs mediated signaling from CD4 + T cells and CD8 + T cells to macrophage-like VSMCs. On the other hand, MIF-(CD74 + CXCR4) mediated signal transmission from contractile VSMCs, T-cell-like VSMCs, and macrophage-like VSMCs to B cells Numerous studies have shown that MIF possesses the function of recruiting and activating macrophages through combining with CD74 and CXCR2 (24)(25)(26) and promote normal cells to acquire an inflammatory phenotype by interacting with the receptor CD74 (27). MIF binds to CD74 + CXCR4, which promotes B-cell migration (28).…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, we anticipate that, on top of interfering with the Fanconi anemia pathway, HSP90 inhibition compromises PDAC cell proliferation and survival by additional mechanisms. For instance, HSP90 inhibition negatively regulates the levels of mutant [ 40 , 41 , 42 ] p53 as well as macrophage migration inhibitory factor (MIF) [ 43 , 44 ]. Such mechanisms might further enhance the efficacy of HSP90 inhibitors, in addition to their cooperation with cisplatin.…”
Section: Discussionmentioning
confidence: 99%